2021
DOI: 10.1097/cce.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Risk Analytic Algorithm to Inform Weaning From Vasoactive Medication in Patients Following Pediatric Cardiac Surgery

Abstract: Advanced clinical decision support tools, such as real-time risk analytic algorithms, show promise in assisting clinicians in making more efficient and precise decisions. These algorithms, which calculate the likelihood of a given underlying physiology or future event, have predominantly been used to identify the risk of impending clinical decompensation. There may be broader clinical applications of these models. Using the inadequate delivery of oxygen index, a U.S. Food and Drug Administration-approved risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a retrospective multicenter study including infants following CPB operations, Futterman et al ( 16 ) showed that a higher IDO 2 index dose over a monitoring period of 2 hours was associated with an increased risk of cardiac arrest even when censoring data 10–30 minutes before the event. Another retrospective multicenter study showed an association between higher IDO 2 index and failure to wean off vasoactive infusions in pediatric patients following cardiac surgery ( 17 ). The prospective phase of this study is underway.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective multicenter study including infants following CPB operations, Futterman et al ( 16 ) showed that a higher IDO 2 index dose over a monitoring period of 2 hours was associated with an increased risk of cardiac arrest even when censoring data 10–30 minutes before the event. Another retrospective multicenter study showed an association between higher IDO 2 index and failure to wean off vasoactive infusions in pediatric patients following cardiac surgery ( 17 ). The prospective phase of this study is underway.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data have been published to date regarding the clinical implications of the IDO2 index. Studies to date demonstrated that the IDO2 index can help identify adverse events in children with sepsis, may assist with evaluating extubation readiness in children after cardiac surgery, may aid in early identi cation of children at risk for cardiorespiratory arrest, may aid in weaning vasoactive medications in children after cardiac surgery [31][32][33][34][35]. It should be noted that while these studies have demonstrated utility of the IDO2 index one study failed to nd that the IDO2 index had prognostic utility [36].…”
Section: Discussionmentioning
confidence: 99%
“…18 The IDO2 index can continue to be computed based on previously acquired data even when data is missing at particular points in time. 19 (Figure 2).…”
Section: Role Of Different Models For Risk Analysis In Picumentioning
confidence: 99%